Assessing Early Childhood Fluid Reasoning in Low- and Middle-Income Nations: Validity of the Wechsler Preschool and Primary Scale of Intelligence Across Seven MAL-ED Sites. (April 2020) - Ruan-Iu, Linda; Pendergast, Laura L.; Rasheed, Muneera; Tofail, Fahmida; Svensen, Erling; Maphula, Angelina; Roshan, Reeba; Nahar, Baitun; Shrestha, Rita; Williams, Brittney; Schaefer, Barbara A.; Scharf, Rebecca; et al.
An adapted version of the Wechsler Preschool and Primary Scale of Intelligence—Third Edition (WPPSI-III) was administered to assess cognitive functioning among 1, 253 5-year-old children from the Malnutrition and Enteric Disease (MAL-ED) study—an international, multisite study investigating multiple aspects of child development. In this study, the factor structure and invariance of the WPPSI-III were examined across seven international research sites located in Bangladesh, Brazil, India, Nepal, Pakistan, South Africa, and Tanzania. Using a multiple indicator multiple cause (MIMIC) modeling approach, the findings supported the validity of a fluid reasoning dimension (comprised of block design, matrix reasoning, and picture completion subscales) across each of the seven sites, although the scores were noninvariant. Accordingly, these scores are recommended for research purposes and understanding relationships between variables but not for mean comparisons or clinical purposes.